Incentive-Compatible Debt Contracts: The One-Period Problem - Gale, Douglas; Hellwig, Martin (Review of Economic Studies, 1985)
In a simple model of borrowing and lending with asymmetric information we show that the optimal, incentive-compatible debt contract is the standard debt contract. The second-best level of investment never exceeds the first-best and is strictly less when there is a positive probability of costly bankruptcy. We also compare the second-best with the results of interest-rate-taking behaviour and consider the effects of risk aversion. Finally we provide conditions under which increasing the borrower's initial net wealth must reduce total investment in the venture.